Metal-ligand complex

By using the metal-ligand complex and bimodal catalyst system of formula I, a polymerization catalyst with improved melt index, melting temperature and molecular weight distribution was prepared, and the problem of difficulty in controlling polymer performance in the prior art was solved.

CN113748140BActive Publication Date: 2025-03-11DOW GLOBAL TECHNOLOGIES LLC
View PDF 24 Cites 0 Cited by

Patent Information

Application Number
CN202080031331.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-17
Filing Date
2020-04-27
Publication Date
2025-03-11
Estimated Expiration
2040-04-27

AI Technical Summary

Technical Problem

In the prior art, when preparing olefin polymerization catalysts, it is difficult to effectively control the melt index, melting temperature and molecular weight distribution of the polymer, which affects the application performance of the polymer.

Method used

A metal-ligand complex, specifically represented as an asymmetric unbridged metallocene complex of formula I, is prepared under activation conditions by contacting an activator, by contacting the activator.

Benefits of technology

It has achieved the preparation of polymers with reduced melt index, increased melt temperature and increased molecular weight, which is suitable for different application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113748140B_ABST
    Figure CN113748140B_ABST
Patent Text Reader

Abstract

Embodiments of the present disclosure relate to metal-ligand complexes of formula I: wherein M is titanium, zirconium or hafnium; R is hydrogen or (C1 to C4) alkyl; R 1 is (C1 to C4) alkyl; R 2 , R 3 , R 4 , R 5 Any one or two of them are independently (C1 to C 20 ) alkyl and R 2 , R 3 , R 4 , R 5 three or two of which are H; and each X is independently halogen, (C1 to C 20 ) alkyl, (C7 to C 20 )aralkyl, (C1 to C6)alkyl-substituted (C6 to C 12 )aryl, (C1 to C6)alkyl-substituted benzyl or silyl-containing group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present disclosure relate to metal-ligand complexes, and more particularly, metal-ligand complexes useful in preparing olefin polymerization catalysts. Background Art

[0002] The polymers are useful in a variety of products including, for example, films, fibers, nonwoven and / or woven fabrics, extruded and / or molded articles, etc. The polymers may be formed by reacting one or more types of monomers in a polymerization reaction in the presence of a polymerization catalyst. Summary of the invention

[0003] The present disclosure provides various embodiments, including:

[0004] A metal-ligand complex of formula I:

[0005]

[0006] wherein M is titanium, zirconium or hafnium; R is hydrogen or (C1 to C4) alkyl; R 1 is (C1 to C4) alkyl; R 2 , R 3 , R 4 , R 5 Any one or two of them are independently (C1 to C 20 ) alkyl and R 2 , R 3 , R 4 , R 5 three or two of which are H; and each X is independently halogen, (C1 to C 20 ) alkyl, (C7 to C 20 )aralkyl, (C1 to C6)alkyl-substituted (C6 to C 12 )aryl, (C1 to C6)alkyl-substituted benzyl or silyl-containing group.

[0007] A bimodal catalyst system comprising the metal-ligand complex of formula I and a bis(2-(pentamethylphenylamino)ethyl)-amine zirconium complex of formula III:

[0008]

[0009] Where M is Zr and each R 1 are independently Cl, Br, (C1 to C 20 )alkyl, (C1 to C6)alkyl-substituted (C6-C 12 )aryl, benzyl or benzyl substituted with (C1 to C6) alkyl.

[0010] A method for preparing a polymerization catalyst, the method comprising contacting the metal-ligand complex of formula I or the bimodal catalyst system with an activator under activation conditions to activate the metal-ligand complex or the bimodal catalyst system, thereby preparing the polymerization catalyst.

[0011] A method for preparing a polyolefin polymer, the method comprising contacting an olefin with a polymerization catalyst under polymerization conditions to polymerize the olefin, thereby preparing a polyolefin polymer.

[0012] A polyolefin polymer is produced by a preparation method thereof. DETAILED DESCRIPTION

[0013] The metal-ligand complex disclosed herein can be represented by Formula I:

[0014]

[0015] wherein M is titanium, zirconium or hafnium; R is hydrogen or (C1 to C4) alkyl; R 1 is (C1 to C4) alkyl; R 2 , R 3 , R 4 , R 5 Any one or two of them are independently (C1 to C 20 ) alkyl and R 2 , R 3 , R 4 , R 5 three or two of which are H; and each X is independently halogen, (C1 to C 20 ) alkyl, (C7 to C 20 )aralkyl, (C1 to C6)alkyl-substituted (C6 to C 12 )aryl, (C1 to C6)alkyl-substituted benzyl or silyl-containing group.

[0016] Metal-ligand complexes can be used to prepare polymerization catalysts, such as asymmetric unbridged metallocene polymerization catalysts. For example, metal-ligand complexes can be contacted with an activator under activation conditions to activate the metal-ligand complex, thereby preparing a polymerization catalyst. Embodiments provide a method for preparing a polymerization catalyst, the method comprising contacting a metal-ligand complex or a bimodal catalyst system of formula I with an activator under activation conditions to activate the metal-ligand complex or the bimodal catalyst system, thereby preparing a polymerization catalyst. The polymerization catalyst prepared by only one metal-ligand complex is suitable for preparing a polyolefin polymer characterized by a unimodal molecular weight distribution. The polymerization catalyst prepared by a bimodal catalyst system is suitable for preparing a polyolefin polymer characterized by a bimodal molecular weight distribution.

[0017] Surprisingly, polymerization catalysts prepared from metal-ligand complexes can help provide polymers having improved, i.e., reduced melt index ((I2); D1238-13 (190° C., 2.16 kg load)) compared to polymers formed under similar polymerization conditions using other asymmetric unbridged metallocene (not of the present invention) polymerization catalysts. Reduced melt index is desirable in some applications.

[0018] Furthermore, unexpectedly, polymerization catalysts prepared from metal-ligand complexes can provide polymers having improved, ie, increased, melting temperatures compared to polymers formed under similar polymerization conditions using other asymmetric unbridged metallocene polymerization catalysts. Increased melting temperatures are desirable in some applications.

[0019] In addition, the polymerization catalysts prepared from the metal-ligand complexes can help provide polymers with improved, i.e., increased molecular weights (Mn, Mw, and / or Mz) compared to polymers formed under similar polymerization conditions using other asymmetric unbridged metallocene polymerization catalysts. Increased molecular weights (Mn, Mw, and / or Mz) are desirable in some applications.

[0020] Furthermore, polymerization catalysts prepared from metal-ligand complexes can help provide polymers having improved, ie, increased, density compared to polymers formed under similar polymerization conditions using other asymmetric unbridged metallocene polymerization catalysts. Increased density is desirable in some applications.

[0021] As described above, R is hydrogen or (C1 to C4) alkyl. One or more embodiments provide that R is (C1 to C3) alkyl. One or more embodiments provide that R is (C1 to C2) alkyl. One or more embodiments provide that R is C1 alkyl. One or more embodiments provide that R is C2 alkyl. One or more embodiments provide that R is C3 alkyl. One or more embodiments provide that R is C4 alkyl.

[0022] As mentioned above, R 1 is (C1 to C4) alkyl. One or more embodiments provide that: R 1 is (C1 to C3) alkyl. One or more embodiments provide that: R 1 is (C1 to C2) alkyl. One or more embodiments provide that: R 1 is a C1 alkyl group. One or more embodiments provide that: R 1 is a C2 alkyl group. One or more embodiments provide that: R 1 is a C3 alkyl group. One or more embodiments provide that: R 1 It is a C4 alkyl group.

[0023] As mentioned above, R 2, R 3 , R 4 , R 5 Any one or two of them are independently (C1 to C 20 ) alkyl and R 2 , R 3 , R 4 , R 5 Three or two of are H. One or more embodiments provide that: R 2 , R 3 , R 4 , R 5 Any one or two of them are independently (C1 to C 10 ) alkyl and R 2 , R 3 , R 4 , R 5 Three or two of are H. One or more embodiments provide that: R 2 , R 3 , R 4 , R 5 Any one or two of them are independently (C1 to C6) alkyl and R 2 , R 3 , R 4 , R 5 Three or two of are H. One or more embodiments provide that: R 2 , R 3 , R 4 , R 5 Any one or two of them are independently (C1 to C3) alkyl and R 2 , R 3 , R 4 , R 5 Three or two of are H. One or more embodiments provide that: R 2 , R 3 , R 4 , R 5 Any one or two of them are independently (C1 to C2) alkyl and R 2 , R 3 , R 4 , R 5 Three or two of are H. One or more embodiments provide that: R 2 , R 3 , R 4 , R 5 Any one or both of them are independently C1 alkyl and R 2 , R 3 , R 4 , R 5 Three or two of them are independently H.

[0024] As described above, each X is independently a halogen, (C1 to C 20 ) alkyl, (C7 to C 20 )aralkyl, (C1 to C6)alkyl-substituted (C6 to C 12 ) aryl, (C1 to C6) alkyl-substituted benzyl or silyl-containing group. One or more embodiments provide that: each X is independently C l One or more embodiments provide that: each X is independently (C1 to C 20 ) alkyl. One or more embodiments provide that: each X is independently (C1 to C 15 ) alkyl. One or more embodiments provide that: each X is independently (C1 to C 10 )alkyl. One or more embodiments provide that each X is independently (C1 to C5)alkyl. One or more embodiments provide that each X is independently C1 alkyl. One or more embodiments provide that each X is independently a silyl-containing group. One or more embodiments provide that each X is independently trihydrocarbylsilylmethyl. One or more embodiments provide that each X is independently trimethylsilylmethyl.

[0025] The metal-ligand complex of formula I may be referred to as a metallocene complex. Examples of the metal-ligand complex of formula I include, but are not limited to: cyclopentadienyl (1,4,7-trimethylindenyl) zirconium dichloride; cyclopentadienyl (1,5,7-trimethylindenyl) zirconium dichloride; methylcyclopentadienyl (1,4,-dimethylindenyl) zirconium dichloride; methylcyclopentadienyl (1,6,-dimethylindenyl) zirconium dichloride; methylcyclopentadienyl (1,7,-dimethylindenyl) zirconium dichloride; methylcyclopentadienyl (1,4,7-trimethylindenyl) zirconium dichloride; methylcyclopentadienyl (1,5,7-trimethylindenyl) zirconium dichloride; propylcyclopentadienyl (1, 5-dimethylindenyl) zirconium dichloride; propylcyclopentadienyl (1,6,-dimethylindenyl) zirconium dichloride; propylcyclopentadienyl (1,7,-dimethylindenyl) zirconium dichloride; propylcyclopentadienyl (1,4,7-trimethylindenyl) zirconium dichloride; propylcyclopentadienyl (1,5,7-trimethylindenyl) zirconium dichloride, cyclopentadienyl (1,5-dimethylindenyl) zirconium dichloride; methylcyclopentadienyl (1,5-dimethylindenyl) zirconium dichloride; cyclopentadienyl (1,5-dimethylindenyl) zirconium dimethyl; and methylcyclopentadienyl (1,5-dimethylindenyl) zirconium dimethyl.

[0026] One or more embodiments provide that the metal-ligand complex of Formula I comprises a disubstituted indenyl, for example, wherein each indenyl substitution is independently (C1 to C4) alkyl. For example, the metal-ligand complex can comprise a disubstituted indenyl, a 1,5-disubstituted indenyl, a 1,6-disubstituted indenyl, or a 1,7-disubstituted indenyl. As used herein, the following indenyl numbering is used:

[0027]

[0028] As mentioned above, and as shown in Figure 1, R 1 It is a (C1 to C4) alkyl group. In addition, as shown in Figure 1, the 2-position and 3-position of the five-membered ring of the indenyl group are each substituted by hydrogen. Therefore, the metal-ligand complex of Formula I can be referred to as an asymmetric unbridged metal-ligand complex. Asymmetric unbridged metal-ligand complexes are a specific class of metal-ligand complexes required for many applications. As known in the art, when stored as an activated supported catalyst preparation, the asymmetric unbridged metal-ligand complex can advantageously have excellent stability; can be used to produce polyethylene polymers with zero, undetectable or very low levels of long-chain branching; and can be operated in a gas phase reactor in such a manner that the incidence of fouling and / or sheeting is reduced compared to other catalysts and / or can be controlled by known methods.

[0029] One or more embodiments provide that the metal-ligand complex disclosed herein can be represented by Formula II:

[0030]

[0031] wherein R is hydrogen or (C1 to C2) alkyl, M is titanium, zirconium or hafnium, and wherein each X is independently halo, (C1 to C2) 20 ) alkyl, (C7 to C 20 )aralkyl, (C1 to C6)alkyl-substituted (C6 to C 12 ) aryl, (C1 to C6) alkyl substituted benzyl or silyl. As shown in formula II, as shown in formula I, R 1 is a C1 alkyl group, such as R 2 is hydrogen, such as R shown in formula I 3 is hydrogen, such as R shown in formula I 4 is a C1 alkyl group, and as shown in Formula I, R 5 It's hydrogen.

[0032] For example, the metal-ligand complex of Formula II can be referred to as cyclopentadienyl (1,5-dimethylindenyl) zirconium dimethyl, e.g., when R is hydrogen, M is zirconium, and each X is a C1 alkyl group; or the metal-ligand complex of Formula II can be referred to as methylcyclopentadienyl (1,5-dimethylindenyl) zirconium dimethyl, e.g., when R is a C1 alkyl group, M is zirconium, and each X is a C1 alkyl group.

[0033] As shown in Formula I and Formula II, R can be hydrogen or (C1 to C4) alkyl. One or more embodiments provide that R is hydrogen. One or more embodiments provide that R is (C1 to C4) alkyl. For example, R can be: C1 alkyl, such as methyl; C2 alkyl; C3 alkyl, such as propyl; or C4 alkyl, such as butyl. When there are enough carbon atoms, "alkyl" can be straight chain, branched, or when there are enough carbon atoms, "alkyl" can be a cyclic paraffin group lacking one hydrogen. Thus, for example, a CH3 group ("methyl") and a CH3CH2 group ("ethyl") are examples of alkyl groups.

[0034] As shown in Formula I and Formula II, M can be titanium, zirconium or hafnium. One or more embodiments provide that M is titanium. One or more embodiments provide that M is zirconium. One or more embodiments provide that M is hafnium.

[0035] As described above, each X shown in Formula I and Formula II is independently a halogen, (C1 to C 20 ) alkyl, (C7 to C 20 )aralkyl, (C1 to C6)alkyl-substituted (C6 to C 12 ) aryl, (C1 to C6) alkyl-substituted benzyl or silyl-containing group. One or more embodiments provide that each X is a halogen group, such as C l One or more embodiments provide that each X is (C1 to C3) alkyl, such as C1 alkyl, C2 alkyl, or C3 alkyl. One or more embodiments provide that each X is benzyl.

[0036] As used herein, "substituted" indicates that the group following the term has at least one moiety replacing one or more hydrogens at any position, the moiety being selected from groups such as halogen groups, hydroxyl groups, carbonyl groups, carboxyl groups, amine groups, phosphino groups, alkoxy groups, phenyl groups, naphthyl groups, C1 to C 20 Alkyl, C2 to C 10 Alkenyl and combinations thereof.

[0037] The metal-ligand complexes of formula I, including the metal-ligand complexes of formula II, can be prepared using the reactants mentioned herein. The metal-ligand complexes of formula I can be prepared by a variety of methods, for example using conventional solvents, reaction conditions, reaction times and isolation procedures used to prepare known metallocenes.

[0038] One or more embodiments provide polymerization catalysts. The polymerization catalyst can be prepared by contacting a metal-ligand complex of a complex of Formula I with an activator under activation conditions to provide a polymerization catalyst, such as an activated metal-ligand complex of Formula I. Activation conditions are well known in the art.

[0039] As used herein, "activator" refers to any supported or unsupported compound or combination of compounds, which can, for example, activate the complex or catalyst component by generating a cationic species of the catalyst component. For example, this can include capturing at least one leaving group, such as "X" group described herein, from the metal center of the complex / catalyst component (e.g., a metal complex of Formula I). ​​Activator may also be referred to as "co-catalyst". As used herein, "leaving group" refers to one or more chemical moieties that are combined with a metal atom and can be captured by an activator, thereby generating a substance that is active for olefin polymerization.

[0040] The activator may include a Lewis acid or a non-coordinating ionic activator or an ionizing activator, or any other compound including a Lewis base, an alkyl aluminum, and / or a conventional type cocatalyst. In addition to the methylaluminoxane ("MAO") and modified methylaluminoxane ("MMAO") mentioned above, illustrative activators may include, but are not limited to, aluminoxanes or modified aluminoxanes and / or ionizing neutral or ionic compounds such as dimethylanilinium tetrakis(pentafluorophenyl)borate, triphenylcarbonium tetrakis(pentafluorophenyl)borate, dimethylanilinium tetrakis(3,5-(CF3)2phenyl)borate, triphenylcarbonium tetrakis(3,5-(C F3) 2-phenyl) borate, dimethylanilinium tetra(perfluoronaphthyl)borate, triphenylcarbonium tetra(perfluoronaphthyl)borate, dimethylanilinium tetra(pentafluorophenyl)aluminate, triphenylcarbonium tetra(pentafluorophenyl)aluminate, dimethylanilinium tetra(perfluoronaphthyl)aluminate, triphenylcarbonium tetra(perfluoronaphthyl)aluminate, tri(perfluorophenyl)boron, tri(perfluoronaphthyl)boron, tri(perfluorophenyl)aluminum, tri(perfluoronaphthyl)aluminum or any combination thereof.

[0041] Aluminoxanes can be described as oligomeric aluminum compounds having -A1(R)-O- subunits, wherein R is an alkyl group. Examples of aluminoxanes include, but are not limited to, methylaluminoxane ("MAO"), modified methylaluminoxane ("MMAO"), ethylaluminoxane, isobutylaluminoxane, or a combination thereof. Aluminoxanes can be produced by hydrolyzing the corresponding trialkylaluminum compound. MMAO can be produced by hydrolyzing trimethylaluminum and a higher carbon trialkylaluminum (such as triisobutylaluminum). There are a variety of known methods for preparing aluminoxanes and modified aluminoxanes. Aluminoxanes can include 3A-type modified methylaluminoxane ("MMAO") (commercially available from Akzo Chemicals, Inc. under the trade name Modified Methylaluminoxane type 3A, as discussed in U.S. Pat. No. 5,041,584). The source of MAO can be a solution having, for example, about 1 wt % to about 50 wt % MAO. Commercially available MAO solutions may include 10 wt % and 30 wt % MAO solutions available from Albemarle Corporation, of Baton Rouge, La.

[0042] One or more organoaluminum compounds, such as one or more alkylaluminum compounds, may be used in combination with aluminoxanes. Examples of alkylaluminum compounds include, but are not limited to, diethylaluminum ethoxide, diethylaluminum chloride, diisobutylaluminum hydride, and combinations thereof. Examples of other alkylaluminum compounds (e.g., trialkylaluminum compounds) include, but are not limited to, trimethylaluminum, triethylaluminum ("TEAL"), triisobutylaluminum ("TiBAl"), tri-n-hexylaluminum, tri-n-octylaluminum, tripropylaluminum, tributylaluminum, and combinations thereof.

[0043] Polymerization catalysts made from the metal-ligand complexes of the complexes of Formula I can be used to prepare polymers. For example, a polymerization catalyst and an olefin can be contacted under polymerization conditions to form a polymer, such as a polyolefin polymer.

[0044] As used herein, a "polymer" has two or more identical or different polymer units derived from one or more different monomers, such as homopolymers, copolymers, terpolymers, etc. A "homopolymer" is a polymer having identical polymer units. A "copolymer" is a polymer having two or more polymer units that are different from each other. A "terpolymer" is a polymer having three polymer units that are different from each other. "Different" with respect to polymer units indicates that the polymer units differ from each other by at least one atom or isomer. Thus, as used herein, the definition of a copolymer includes terpolymers, etc. As used herein, a "polymerization process" is a process for forming a polymer.

[0045] Embodiments provide that: polymer can be a polyolefin polymer. As used herein, "olefin" which may be referred to as "alkene" refers to a linear, branched or cyclic compound including carbon and hydrogen and having at least one double bond. As used herein, when a polymer or copolymer is referred to as comprising olefins (e.g., prepared by olefins), the olefins present in such polymers or copolymers are olefins in polymerized form. For example, when it is said that the ethylene content of the copolymer is 75% to 85% by weight, it is understood that the polymer units in the copolymer are derived from ethylene in the polymerization reaction, and the derived units are present in 75% to 85% by weight, based on the gross weight of the polymer. High carbon alpha-olefins refer to alpha-olefins with 3 or more carbon atoms.

[0046] Polyolefins include polymers prepared from olefin monomers such as ethylene, i.e. polyethylene and straight or branched high-carbon alpha-olefin monomers containing 3 to 20 carbon atoms. Examples of high-carbon alpha-olefin monomers include, but are not limited to, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene and 3,5,5-trimethyl-1-hexene. Examples of polyolefins include ethylene polymers with at least 50% by weight of ethylene, including ethylene-1-butene, ethylene-1-hexene and ethylene-1-octene copolymers, etc. Other monomers that can be used include, for example, ethylenically unsaturated monomers, dienes with 4 to 18 carbon atoms, conjugated or non-conjugated dienes, polyenes, vinyl monomers and cycloolefins. Examples of monomers may include, but are not limited to, norbornene, norbornadiene, isobutylene, isoprene, vinylbenzocyclobutane, styrene, alkyl-substituted styrene, ethylidene norbornene, dicyclopentadiene and cyclopentane. In many embodiments, copolymers of ethylene can be produced where a comonomer having at least one alpha-olefin having 4 to 15 carbon atoms, preferably 4 to 12 carbon atoms, and most preferably 4 to 8 carbon atoms is polymerized with ethylene, for example, in a gas phase polymerization process. In another embodiment, ethylene and / or propylene can be polymerized with at least two different comonomers, any one of which can be a diene, to form a terpolymer.

[0047] One or more embodiments provide that the polymer may include from 50% to 99.9% by weight of units derived from ethylene, based on the total weight of the polymer. All individual values ​​and subranges from 50% to 99.9% by weight are included; for example, based on the total weight of the polymer, the polymer may include from a lower limit of 50%, 60%, 70%, 80%, or 90% by weight of units derived from ethylene to an upper limit of 99.9%, 99.7%, 99.4%, 99%, 96%, 93%, 90%, or 85% by weight of units derived from ethylene. Based on the total weight of the polymer, the polymer may include from 0.1% to 50% by weight of units derived from a comonomer.

[0048] As described above, unexpectedly, the polymerization catalyst prepared from the metal-ligand complex of Formula I can help provide a polymer having an improved, i.e., reduced melt index ((I2); D1238-13 (190° C., 2.16 kg load)) compared to polymers formed with other polymerization catalysts under similar polymerization conditions. For example, when the two polymerizations occur at the same polymerization temperature, the same hydrogen concentration and / or the same comonomer to monomer ratio, the polymerization catalyst prepared from the metal-ligand complex can help provide a polymer having a reduced melt index ((I2); D1238-13 (190° C., 2.16 kg load)) compared to polymers formed with other polymerization catalysts.

[0049] In addition, as described above, unexpectedly, the polymerization catalyst prepared from the metal-ligand complex of Formula I can help provide polymers with improved, i.e., increased melting temperatures compared to polymers formed with other polymerization catalysts under similar polymerization conditions. For example, when the two polymerizations occur at the same polymerization temperature, the same hydrogen concentration, and / or the same comonomer to monomer ratio, the polymerization catalyst prepared from the metal-ligand complex can help provide polymers with increased melting temperatures compared to polymers formed with other polymerization catalysts.

[0050] Embodiments provide that the polymer may have a melt index (I2) in the range of 0.001 g / 10 min to 1000 g / 10 min as measured by D1238-13 (at 190° C., 2.16 kg load). For example, the polymer may have a melt index of 0.001 g / 10 min to 500 g / 10 min, or 0.1 g / 10 min to 320 g / 10 min. Some embodiments provide that the melt index is less than 310, less than 300, less than 290, less than 280, less than 270, less than 260, less than 250, less than 240, less than 230, or less than 220.

[0051] The embodiments provide that the polymer can have an Mn (number average molecular weight) of 5,000 to 75,000. All individual values ​​and subranges from 5,000 to 75,000 are included; for example, the polymer can have an Mn of 5,000; 6,000; 7,000; 7,500; 8,000; or 8,500 to an Mn of 75,000; 65,000; 55,000; 45,000; 35,000; 25,000; 24,000; 23,000; or 22,000. Mn can be determined by gel permeation chromatography (GPC), as is known in the art.

[0052] The embodiments provide that the polymer can have an Mw (weight average molecular weight) of 15,000 to 110,000. All individual values ​​and subranges from 15,000 to 110,000 are included; for example, the polymer can have an Mw with a lower limit of 15,000; 20,000; 22,000; 24,000; 24,500; or 25,000 to an upper limit of 110,000; 100,000; 80,000; 60,000; or 40,000. Mw can be determined by GPC as is known in the art.

[0053] The embodiments provide that the polymer can have an Mz (z-average molecular weight) of 40,000 to 400,000. All individual values ​​and subranges from 40,000 to 400,000 are included; for example, the polymer can have an Mz with a lower limit of 40,000; 44,000; 46,000; 47,000; 48,000; 48,500; or 49,000 to an upper limit of 400,000; 300,000; 200,000; 100,000; or 65,000. Mz can be determined by GPC as is known in the art.

[0054] The embodiments provide that the polymer can have a molecular weight distribution determined as a weight average molecular weight / number average molecular weight (Mw / Mn) of 2.50 to 8.00. All individual values ​​and subranges from 2.50 to 8.00 are included; for example, the polymer can have a Mw / Mn with a lower limit of 2.50; 2.80; 2.90; 3.00; or 3.10 to an upper limit of 8.00; 7.50; 7.00; or 6.50. As known in the art, Mw / Mn can be determined by GPC analysis.

[0055] The embodiments provide that the polymer can have a melting temperature of 100° C. to 165° C. including all individual values ​​and subranges from 100° C. to 165° C.; for example, the polymer can have a melting temperature with a lower limit of 100° C., 110° C., 120° C., 125° C., 128° C., 129° C., 130° C. to an upper limit of 165° C., 160° C., 155° C., 150° C., 140° C., or 135° C. The melting temperature can be determined by differential scanning calorimetry according to ASTM D3418-08.

[0056] The embodiment provides that the polymer may have a 3 Up to 0.970g / cm 3 Density. Including 0.890 to 0.970g / cm 3 All individual values ​​and subranges of; for example, the polymer can have a lower limit of 0.890, 0.900, 0.910, 0.920, 0.930, 0.940, 0.950, 0.957, 0.958, 0.959, or 0.960 g / cm 3 Up to 0.970, 0.966, 0.966 or 0.963 g / cm 3 Density. Density can be determined according to ASTM D-792-13, Standard Test Methods for Density and Specific Gravity (Relative Density) of Plastics by Displacement, Method B (for testing solid plastics in liquids other than water, such as in liquid 2-propanol). The result can be expressed in grams per cubic centimeter (g / cm 3 ) as unit report.

[0057] One or more embodiments provide that the polymer can be a bimodal polymer. For example, the bimodal polymer can include a low molecular weight component, for example, as described herein.

[0058] Gel Permeation Chromatography (GPC) Test Method: Weight Average Molecular Weight Test Method: Mw, number average molecular weight (Mn), and Mw / Mn were determined using chromatograms obtained on a high temperature gel permeation chromatograph (HTGPC, Polymer Laboratories). The HTGPC was equipped with a transfer line, a differential refractive index detector (DRI), and three Polymer Laboratories PLgel 10 μm Mixed-B columns, all contained in an oven maintained at 160°C. Methods A solvent consisting of BHT-treated TCB was used with a nominal flow rate of 1.0 milliliters per minute (mL / min) and a nominal injection volume of 300 microliters (μL). The solvent was prepared by dissolving 6 grams of butylated hydroxytoluene (BHT, antioxidant) in 4 liters (L) of reagent grade 1,2,4-trichlorobenzene (TCB) and filtering the resulting solution through a 0.1 micron (μm) Teflon filter to obtain the solvent. The solvent was degassed with an online degasser before entering the HTGPC instrument. The column was calibrated with a series of monodisperse polystyrene (PS) standards. Separately, a known concentration of the test polymer dissolved in the solvent was prepared by heating a known amount of the test polymer in a known volume of solvent at 160°C and continuously shaking for 2 hours to obtain a solution. (All amounts were measured gravimetrically.) The target solution concentration c of the test polymer was 0.5 mg polymer / ml solution (mg / mL) to 2.0 mg polymer / ml solution, with a lower concentration c being used for higher molecular weight polymers. Before running each sample, the DRI detector was purged. Then, the flow rate in the device was increased to 1.0 mL / min, and the DRI detector was stabilized for 8 hours before the first sample was injected. Mw and Mn were calculated using a universal calibration relationship with the column calibration. The MW under each elution volume was calculated using the following equation: The subscript "X" represents the test sample, the subscript "PS" represents the PS standard, and a PS =0.67, K PS = 0.000175 and a X and K X Obtained from published literature. For polyethylene, a X / K X =0.695 / 0.000579. For polypropylene, a X / K X =0.705 / 0.0002288. At each point in the resulting chromatogram, the DRI signal I minus the baseline was calculated using the following equation: DRI Calculate the concentration c: c = K DRI I DRI / (dn / dc), where K DRIis a constant determined by calibrating DRI, / represents division, and dn / dc is the refractive index increment of the polymer. For polyethylene, dn / dc=0.109. The polymer mass recovery is calculated by the ratio of the integral area at the elution volume of the concentration chromatography chromatogram and the injected mass, and the injected mass is equal to the predetermined concentration multiplied by the injection loop volume. Unless otherwise indicated, all molecular weights are reported in grams / mole (g / mol). Additional details about the method for determining Mw, Mn, and MWD are described in US 2006 / 0173123, pages 24-25, paragraphs

[0334] to

[0341] . The graph of dW / dLog(MW) on the y-axis relative to Log(MW) on the x-axis gives a GPC chromatogram, wherein Log(MW) and dW / dLog(MW) are as defined above.

[0059] The polymers can be used in a variety of articles, such as films, fibers, nonwoven and / or woven fabrics, extruded articles and / or molded articles, and the like.

[0060] A bimodal catalyst system is provided, the bimodal catalyst system comprising a metal-ligand complex of formula I and a bis(2-(pentamethylphenylamino)ethyl)-amine zirconium complex of formula III:

[0061]

[0062] A bimodal catalyst system is also provided, the bimodal catalyst system comprising a metal-ligand complex of formula I or its activated reaction product and at least one olefin polymerization catalyst (second catalyst) that is not a metal-ligand complex of formula I or III or its activated reaction product. This second catalyst can be a Ziegler-Natta catalyst, a chromium-based catalyst (e.g., a so-called Phillips catalyst), a metallocene catalyst without an indenyl ring (e.g., a metallocene catalyst containing an unsubstituted and / or alkyl-substituted cyclopentadienyl ring), a catalyst compound containing a Group 15 metal described in paragraphs

[0041] to

[0046] of WO2018 / 064038A1, or a biphenol catalyst compound described in paragraphs

[0036] to

[0080] of US20180002464A1.

[0063] The metal-ligand complex of formula I and other components discussed herein, such as activators and / or additional polymeric components, can be used with a support. "Support" may also be referred to as "carrier" and refers to any support material, including porous support materials (such as talc), inorganic oxides, and inorganic chlorides.

[0064] The metal-ligand complex of formula I and other components discussed herein can be supported on the same or separate supports, or one or more components can be used in an unsupported form. The use of supports can be achieved by any technology used in the art. One or more embodiments provide for the use of a spray drying process. Spray drying processes are well known in the art. The support can be functionalized.

[0065] The support can be a porous support material (e.g. talc), an inorganic oxide or an inorganic chloride. Other support materials include resin support materials (e.g. polystyrene), functionalized or cross-linked organic supports (such as polystyrene divinyl benzene polyolefins or polymeric compounds), zeolites, clays or any other organic or inorganic support materials, etc., or mixtures thereof.

[0066] Support materials include inorganic oxides including Group 2, 3, 4, 5, 13 or 14 metal oxides. Some preferred supports include silica, fumed silica, alumina, silica-alumina and mixtures thereof. Some other supports include magnesium oxide, titanium dioxide, zirconium oxide, magnesium chloride, montmorillonite, phyllosilicates, zeolites, talc, clays, etc. Moreover, combinations of these support materials may be used, such as silica-chromium, silica-alumina, silica-titania, etc. Additional support materials may include porous acrylic polymers, nanocomposites, aerogels, spherulites and polymer beads.

[0067] An example of a support is fumed silica available under the trade name Cabosil™ TS-610, or other TS-series or TG-series supports available from Cabot Corporation. Fumed silica is typically silica having a particle size of 7 to 30 nanometers that has been treated with dimethylsilyl dichloride such that most of the surface hydroxyl groups are capped.

[0068] The support material may have a surface area ranging from about 10 m / g to about 700 m / g, a surface area ranging from about 0.1 g / cm 3 To about 4.0g / cm 3 and an average particle size ranging from about 5 μm to about 500 μm. More preferably, the support material has a surface area ranging from about 50 m / g to about 500 m / g and a pore volume of about 0.5 g / cm 3 To about 3.5g / cm 3 and an average particle size of about 10 μm to about 200 μm. Most preferably, the support material has a surface area in the range of about 100 m / g to about 400 m / g and a pore volume of about 0.8 g / cm 3 To about 3.0g / cm 3And the average particle size is about 5 μm to about 100 μm. The average pore size of the carrier generally has a pore size in the range of 10 to 1000 Å, preferably 50 to about 500 Å and most preferably 75 to about 350 Å.

[0069] The metal-ligand complex of formula I and other components discussed herein, such as activators and / or additional polymeric components can be slurried. Slurries are well known in the art. For example, the slurry can include the metal-ligand complex of formula I, an activator, and a support.

[0070] The metal in the activator can be 1000:1 to 0.5:1, 300:1 to 1:1 or 150:1 to 1:1 with the metal-ligand complex of formula I in the slurry and / or the metal in other polymeric components in the mol ratio. One or more diluents, such as fluids, can be used to promote the combination of any two or more components in the slurry. For example, the metal-ligand complex of formula I and the activator can be combined together in the presence of toluene or another non-reactive hydrocarbon or hydrocarbon mixture. In addition to toluene, other suitable diluents can include but are not limited to ethylbenzene, xylene, pentane, hexane, heptane, octane, other hydrocarbons or any combination thereof. Then a carrier dried or mixed with toluene can be added to the mixture, or the metal-ligand complex / activator can be added to the carrier. The slurry can be fed to the reactor for polymerization process, and / or the slurry can be dried, such as spray-dried, before being fed to the reactor for polymerization process.

[0071] The polymerization process can be a suspension polymerization process, a slurry polymerization process and / or a gas phase polymerization process. The polymerization process can utilize known equipment and reaction conditions, such as known polymerization conditions. The polymerization process is not limited to any particular type of polymerization system. For example, at atmospheric pressure, below atmospheric pressure or above atmospheric pressure, the polymerization temperature can be in the range of about 0°C to about 300°C. In particular, a slurry or solution polymerization system can adopt a pressure below atmospheric pressure or alternatively above atmospheric pressure, and a temperature in the range of about 40°C to about 300°C. An embodiment provides a method for preparing a polyolefin polymer, the method comprising: contacting an olefin with a polymerization catalyst as described herein under polymerization conditions to polymerize the olefin, thereby preparing a polyolefin polymer.

[0072] One or more embodiments provide that the polymer may be formed by a gas phase polymerization system at a pressure above atmospheric pressure in the range of 0.07 bar to 68.9 bar, 3.45 bar to 27.6 bar, or 6.89 bar to 24.1 bar, and at a temperature in the range of 30° C. to 130° C., 65° C. to 110° C., 75° C. to 120° C., or 80° C. to 120° C. For one or more embodiments, the operating temperature may be less than 112° C. A stirred and / or fluidized bed gas phase polymerization system may be used.

[0073] Conventionally, conventional fluidized bed gas phase polymerization method can be carried out by continuously passing a stream containing one or more olefin monomers through a fluidized bed reactor at a speed sufficient to maintain a bed of solid particles in a suspended state under reaction conditions and in the presence of a catalyst composition (for example, a composition comprising a metal complex of formula I and an activator). The stream comprising unreacted monomers can be continuously recovered, compressed, cooled, optionally partially or completely condensed from the reactor, and circulated back to the reactor. Product (i.e., polymer) can be taken out from the reactor, and a substitute monomer can be added to the circulating stream. Gases that are inert to catalyst composition and reactants can also be present in the gas stream. The polymerization system can include, for example, a single reactor or two or more reactors in series.

[0074] The feed stream for the polymerization process may include olefin monomers, non-olefin monomers (such as nitrogen and / or hydrogen), and may also include one or more non-reactive alkanes that may be condensed and used to remove heat of reaction during the polymerization process. Illustrative non-reactive alkanes include, but are not limited to, propane, butane, isobutane, pentane, isopentane, hexane, isomers thereof, and derivatives thereof. The feed may enter the reactor at a single or multiple different locations.

[0075] For polymerization process, polymerization catalyst can be continuously fed to reactor.Gases (such as nitrogen or argon) that are inert to polymerization catalyst can be used to bring polymerization catalyst into reactor bed.In one embodiment, polymerization catalyst can be provided in the form of slurry in mineral oil or liquid hydrocarbon or mixture (such as propane, butane, isopentane, hexane, heptane or octane).Slurry can be delivered to reactor together with carrier fluid (such as nitrogen or argon or liquid (such as isopentane or other C3 to C8 alkane)).

[0076] For the polymerization process, hydrogen may be used in a gas mole ratio of hydrogen to ethylene in the reactor ranging from a lower limit of 0.0002, 0.0006, 0.001, 0.0016, 0.002, 0.004 to an upper limit of 0.1, 0.05, 0.01, 0.008, 0.006. Many embodiments utilize hydrogen.

[0077] The polymerization process may use a gas phase polymerization (GPP) reactor, such as a stirred bed gas phase polymerization reactor (SB-GPP reactor) or a fluidized bed gas phase polymerization reactor (FB-GPP reactor), to prepare the polymer. Such reactors and methods are generally well known. For example, FB-GPP reactors / methods may be described in US 3,709,853; US 4,003,712; US 4,011,382; US 4,302,566; US 4,543,399; US 4,882,400; US 5,352,749; US 5,541,270; EP-A-0802 202; and Belgian Patent No. 839,380. These SB-GPP and FB-GPP polymerization reactors and methods mechanically stir or fluidize the polymerization medium inside the reactor by continuous flow of gaseous monomers and diluents, respectively. Other useful reactors / processes contemplated include tandem or multistage polymerization processes such as described in US 5,627,242; US 5,665,818; US 5,677,375; EP-A-0 794 200; EP-B1 -0 649 992; EP-A-0 802 202; and EP-B-634 421.

[0078] Polymerization operating conditions are any variable or combination of variables that may affect the polymerization reaction in the GPP reactor or the composition or properties of the polymer produced therefrom. Variables may include reactor design and dimensions; component composition and amounts; molar ratios of different reactants; presence or absence of feed gas (such as H2 and / or O2), molar ratio of feed gas to reactants, absence or concentration of interfering materials (e.g., H2O), absence or presence of induced condensing agents (ICA), average polymer residence time in the reactor, partial pressures of ingredients, feed rate of monomers, reactor bed temperature (e.g., fluidized bed temperature), nature or sequence of process steps, transition time periods between steps. Variables other than that / those variables described or varied by the process or use may be held constant.

[0079] For the polymerization process, the amount of ethylene ("C2"), hydrogen ("H2"), and 1-hexene ("C6" or "C x ”, where x is 6) to maintain a fixed comonomer to ethylene monomer gas molar ratio (C x / C2, such as C6 / C2), a constant hydrogen to ethylene gas mole ratio ("H2 / C2") equal to a described value (e.g., 0.00200), and a constant ethylene ("C2") partial pressure equal to a described value (e.g., 1,000 kPa). The concentration of the gas can be measured by online gas chromatography to understand and maintain the composition in the recycle gas stream. The reaction bed of growing polymer particles can be maintained in a fluidized state by continuously flowing the make-up feed and recycle gas through the reaction zone. A superficial gas velocity of 0.49 meters per second (m / s) to 0.67 meters per second (1.6 feet per second (ft / s) to 2.2 feet per second) can be used. The FB-GPP reactor can be operated at a total pressure of about 2344 kilopascals (kPa) to about 2413 kilopascals (about 340 pounds per square inch-gauge (psig) to about 350 pounds per square inch-gauge) and at a desired first reactor bed temperature. The fluidized bed can be maintained at a constant height by withdrawing a portion of the bed at a rate equal to the production rate of the bimodal ethylene-co-1-hexene copolymer composition in particle form, which production rate can be from 10 kilograms per hour (kg / hour) to 20 kg / hour. The product (e.g., ethylene-co-1-hexene copolymer composition) can be removed semi-continuously via a series of valves into a fixed volume chamber, wherein this removed bimodal ethylene-co-1-hexene copolymer composition is purged to remove entrained hydrocarbons and treated with a stream of humid nitrogen (N2) gas to deactivate any traces of residual catalyst.

[0080] The catalyst system can be fed into the polymerization reactor in "dry mode" or "wet mode", alternatively dry mode, alternatively wet mode. Dry mode is dry powder or granules. Wet mode is a suspension in an inert liquid such as mineral oil.

[0081] An induced condensing agent (ICA) may be used, such as an inert liquid suitable for cooling materials in a gas phase polymerization reactor. The ICA may be (C5-C 20 ) alkane, for example, 2-methylbutane (i.e., isopentane). Aspects of the method using ICA can be referred to as induced condensing mode operation (ICMO). ICMO is described in US 4,453,399; US 4,588,790; US 4,994,534; US 5,352,749; US 5,462,999; and US 6,489,408. The ICA concentration in the gas phase can be measured using gas chromatography by calibrating the peak area percentage to molar percentage (mol%) with a gas mixture standard of known concentrations of the gas phase components. The ICA concentration can be from 1 mol% to 10 mol%.

[0082] The polymerization process conditions may also include one or more additives, such as chain transfer agents or promoters. Chain transfer agents are well known and may be metal alkyls, such as diethyl zinc. Promoters are such as known in US 4,988,783 and may include chloroform, CFCl3, trichloroethane and difluorotetrachloroethane. Before the reactor is started, a scavenger may be used to react with moisture, and during the reactor conversion, a scavenger may be used to react with excess activator. The scavenger may be trialkylaluminum. Gas phase polymerization may be operated without (non-intentionally added) scavengers. The polymerization conditions for the gas phase polymerization reactor / process may also include a certain amount (e.g., 0.5 ppm to 200 ppm based on all feeds entering the reactor) of an electrostatic control agent and / or a continuity additive, such as aluminum stearate or polyethylene imine. An electrostatic control agent may be added to the FB-GPP reactor to suppress the formation or accumulation of static charge therein.

[0083] The polymerization process can use a pilot scale fluidized bed gas phase polymerization reactor (pilot reactor), which includes the following reactor vessel: a fluidized bed containing a bimodal ethylene-co-1-hexene copolymer composition powder and a distributor plate disposed above the bottom head, and defining a bottom gas inlet, and having an amplification zone or cyclone system at the top of the reactor vessel to reduce the amount of resin fines that may escape from the fluidized bed. The amplification zone can define a gas outlet. The pilot reactor can also include a compressed blower with sufficient power to continuously circulate or annularly flow the surrounding gas downward from the gas outlet in the amplification zone in the top of the reactor vessel, reach and enter the bottom gas inlet of the pilot reactor and pass through the distributor plate and the fluidized bed. The pilot reactor can also include a cooling system to remove the heat of polymerization and maintain the fluidized bed at a target temperature. The gas composition such as ethylene, α-olefins (e.g., 1-hexene) and hydrogen fed to the pilot reactor can be monitored by online gas chromatography in the circulation loop to maintain a specific concentration that defines the polymer properties and can control the polymer properties. The catalyst system can be fed into the pilot reactor from a high pressure device in the form of a slurry or a dry powder, wherein the slurry is fed via a syringe pump and the dry powder is fed via a metering disk. The catalyst system typically enters the fluidized bed below 1 / 3 of its bed height. The pilot reactor may also include a means for weighing the fluidized bed and an isolation port (product discharge system) for discharging the bimodal ethylene-co-1-hexene copolymer composition powder from the reactor vessel in response to the fluidized bed weight that increases as the polymerization reaction proceeds.

[0084] In some embodiments, the FB-GPP reactor is a commercial scale reactor, such as the UNIPOL reactor available from Univation Technologies, LLC, a subsidiary of The Dow Chemical Company, Midland, Michigan, USA. TM Reactor or UNIPOL TM II reactor.

[0085] Various aspects of the disclosure are provided as follows.

[0086] Aspect 1 provides a metal-ligand complex of formula I:

[0087]

[0088] wherein M is titanium, zirconium or hafnium; R is hydrogen or (C1 to C4) alkyl; R 1 is (C1 to C4) alkyl; R 2 , R 3 , R 4 , R 5 Any one or two of them are independently (C1 to C 20 ) alkyl and R 2 , R 3 , R 4 , R 5 three or two of which are H; and each X is independently halogen, (C1 to C 20 ) alkyl, (C7 to C 20 )aralkyl, (C1 to C6)alkyl-substituted (C6 to C 12 )aryl, (C1 to C6)alkyl-substituted benzyl or silyl-containing group.

[0089] Aspect 2 provides a metal-ligand complex of formula II:

[0090]

[0091] wherein R is hydrogen or (C1 to C2) alkyl, M is titanium, zirconium or hafnium, and wherein each X is independently halo, (C1 to C2) 20 ) alkyl, (C7 to C 20 )aralkyl, (C1 to C6)alkyl-substituted (C6 to C 12 )aryl, (C1 to C6)alkyl-substituted benzyl or silyl-containing group.

[0092] Aspect 3 provides the metal-ligand complex according to aspect 1 or aspect 2, wherein R is hydrogen.

[0093] Aspect 4 provides the metal-ligand complex according to aspect 1 or aspect 2, wherein R is a (C1 to C2) alkyl group.

[0094] Aspect 5 provides the metal-ligand complex according to any one of aspects 1 and 4, wherein R is methyl.

[0095] Aspect 6 provides the metal-ligand complex according to any one of aspects 1 and 4, wherein R is ethyl.

[0096] Aspect 7 provides the metal-ligand complex according to any one of aspects 1 to 6, wherein M is Zr.

[0097] Aspect 8 provides the metal-ligand complex according to any one of aspects 1 to 7, wherein each X is independently Cl, (C1 to C3) alkyl or benzyl.

[0098] Aspect 9 provides the metal-ligand complex according to aspect 1 or aspect 2, wherein the metal-ligand complex is selected from the following:

[0099] , wherein R is hydrogen, M is zirconium, and each X is Cl;

[0100] , wherein R is methyl, M is zirconium, and each X is Cl;

[0101] , wherein R is ethyl, M is zirconium, and each X is Cl;

[0102] , wherein R is hydrogen, M is zirconium, and each X is methyl;

[0103] , wherein R is methyl, M is zirconium, and each X is methyl; and

[0104] , wherein R is ethyl, M is zirconium, and each X is methyl.

[0105] Aspect 10 provides a bimodal catalyst system, comprising the metal-ligand complex according to any one of aspects 1 to 9 and a bis(2-(pentamethylphenylamino)ethyl)-amine zirconium complex of formula III:

[0106]

[0107] Where M is Zr and each R 1 are independently Cl, Br, (C1 to C 20 )alkyl, (C1 to C6)alkyl-substituted (C6-C 12 )aryl, benzyl or benzyl substituted with (C1 to C6) alkyl.

[0108] Aspect 11 provides a method for preparing a polymerization catalyst, the method comprising contacting the metal-ligand complex according to any one of Aspects 1 to 9 or the bimodal catalyst system according to Aspect 10 with an activator under activation conditions to activate the metal-ligand complex or the bimodal catalyst system, thereby preparing the polymerization catalyst.

[0109] Aspect 12 provides the method according to aspect 11, wherein the activator is methylaluminoxane.

[0110] Aspect 14 provides a polymerization catalyst prepared by the method according to any one of aspects 11 to 12.

[0111] Aspect 14 provides a method for preparing a polyolefin polymer, the method comprising:

[0112] The polyolefin polymer is prepared by contacting an olefin with the polymerization catalyst according to aspect 13 under polymerization conditions to polymerize the olefin.

[0113] Aspect 15 provides a polyolefin polymer prepared by the method according to aspect 14.

[0114] Aspect 16 provides the metal-ligand complex according to any one of aspects 1 to 6, wherein M is zirconium or hafnium.

[0115] Example

[0116] 3,6-dimethyl-1H-indene, which can be represented by the following formula:

[0117]

[0118] Prepared as follows. 3,6-Dimethyl-1H-indene can form an anion upon deprotonation, which anion can be referred to as 1,5-dimethyl-indenyl. In a glove box, tetrahydrofuran (25 mL) and methylmagnesium bromide (2 eq, 18.24 mL, 54.72 mmol) were charged to a 250-mL two-necked container equipped with a thermometer (side neck) and a solid addition funnel. The contents of the container were cooled in a freezer set at -35°C for 40 minutes; when removed from the freezer, the contents of the container measured -12°C. While stirring, indanone [5-methyl-2,3-dihydro-1H-inden-1-one (Catalog # HC-2282)] (1 eq, 4.000 g, 27.36 mmol) was added to the container in small portions as a solid, and the temperature increased due to the exothermic reaction; the addition was controlled to keep the temperature at or below room temperature. Once the addition is complete, the funnel is removed and the sealed container (SUBA). The sealed container is moved to a fume hood (wherein the contents are already at room temperature) and placed under a nitrogen purge, then stirred for 3 hours. Remove the nitrogen purge, ether (25mL) is added to the container to replace the evaporated solvent, and then the reaction is cooled using acetone / ice bath. Addition funnel is used to add HCl (15% volume) solution (9 equivalents, 50.67mL, 246.3mmol) very slowly to the contents of the container, maintaining the temperature below 10°C. Then, the contents of the container are slowly heated up for about 12 hours (bath in place). Then, the contents of the container are transferred to a separating funnel and each phase is separated. Wash the aqueous phase with ether (3×25mL). Then wash the combined organic phase with sodium bicarbonate (50mL, saturated aqueous solution), water (50mL) and saline (50mL). The organic phase is dried over magnesium sulfate, filtered and the solvent is removed by a rotary evaporator. The resulting dark oil, confirmed as the product by NMR, was dissolved in pentane (25 mL) and then filtered through a short plug of silica gel capped with sodium sulfate (pre-wet with pentane). Additional pentane (25-35 mL) was used to rinse the plug and then combined with the first. The solution was dried on a rotary evaporator to give 2.87 g (74% yield) of 3,6-dimethyl-1H-indene, confirmed as the product by NMR. 1 H NMR (C6D6): δ7.18 (d, 1H), 7.09 (s, 1H), 7.08 (d, 1H), 5.93 (multiplet, 1H), 3.07 (multiplet, 2H), 2.27 (s, 3H), 2.01 (q, 3H).

[0119] Example 1, cyclopentadienyl (1,5-dimethylindenyl) zirconium dimethyl was prepared as follows. In a glove box, 3,6-dimethyl-1H-indene (1.000 g, 6.94 moles) in dimethoxyethane (10 mL) was added to a 4 ounce container, which was then capped and the contents of the container were frozen to -35°C. Butyl lithium (1.6 M hexane, 4.3 mL, 0.0069 moles) was added to the container and the contents were stirred for approximately 3 hours while removing heat to maintain the contents of the container at approximately -35°C. The reaction mixture was stirred for 3 hours by dissolving a small aliquot in d8-THF. 1 The progress of the reaction was monitored by H NMR analysis; when the reaction was complete, solid cyclopentadienyl zirconium trichloride (CpZrCl3) (1.821 g) was added portionwise to the contents of the vessel while stirring. The reaction was carried out by dissolving a small aliquot in d8-THF. 1 The progress of the reaction was monitored by H NMR analysis; the reaction was complete after approximately 3 hours, and the contents of the vessel were stirred for approximately an additional 12 hours. Methylmagnesium bromide (3.0 M in diethyl ether, 4.6 mL) was then added to the contents of the vessel, and the contents of the vessel were stirred for approximately 12 hours after the addition. The solvent was then removed in vacuo, and the product was extracted into hexanes (40 mL) and filtered through celite, washed with additional hexanes (30 mL), and then dried in vacuo to provide cyclopentadienyl(1,5-dimethylindenyl)zirconium dimethyl. Cyclopentadienyl(1,5-dimethylindenyl)zirconium dimethyl was obtained by 1 H NMR analysis confirmed. 1 H NMR (C6D6): δ7.26 (d, 1H), 6.92 (d, 1H), 6.83 (dd, 1H), 5.69 (d, 1H), 5.65 (multiplet, 1H), 5.64 (s, 5H), 2.18 (s, 3H), 2.16 (s, 3H), -0.34 (s, 3H), -0.62 (s, 3H).

[0120] Example 2, cyclopentadienyl (1,5-dimethylindenyl) zirconium dichloride was prepared as follows. In a glove box, 3,6-dimethyl-1H-indene (5.00 g, 34.7 mmol) and hexane (100 mL) were loaded into a container. While stirring with a magnetic stirring bar, n-butyl lithium (1.6 M in hexane, 23.8 mL, 38.1 mmol) was slowly added to the contents of the container, which was then stirred for approximately 12 hours to obtain a precipitate observed as a white solid. The precipitate was collected by filtration, washed with hexane (3×20 mL), and dried in vacuo to obtain 1,5-dimethylindenyl lithium (4.88 g, 93.7% yield), which was observed as a white solid.

[0121] Then, in a glove box, a portion of 1,5-dimethyl indenyl lithium (2.315 g, 15.42 mmol) was dissolved in dimethoxyethane (60 mL) in a container, and then CpZrCl (4.05 g, 15.42 mmol) was added in batches as a solid. After stirring for about 12 hours, the solvent was removed in vacuo and the contents in the container were dissolved in toluene (110 mL) and filtered at 60 ° C. Then, NMR analysis of the aliquot indicated the desired product. In order to purify the product, the filtrate volume was reduced to 40 mL in a vacuum, and the temperature was raised to 80 ° C to dissolve. The solution was then slowly cooled to room temperature and then stored in a glove box freezer (-32°C) to precipitate the recrystallized product, which was collected by filtration and washed with hexane (2×10 mL) and then dried in vacuo to give cyclopentadienyl (1,5-dimethylindenyl) zirconium dichloride, observed as a bright yellow solid (4.09 g, 71.6%). 1 H NMR(C6D6): d7.32(m,1H),6.90(dt,1H),6.75(dd,1H),6.19(dq,1H),5.76(s,5H),5.73(m,1H),2.35(d,3H),2.08(d,3H).

[0122] Embodiment 3, methylcyclopentadienyl (1,5-dimethylindenyl) zirconium dichloride is prepared as follows.1,5-dimethylindenyl lithium is prepared as described in Example 2.In a glove box, 1,5-dimethylindenyl lithium (0.500g, 3.33mmol) is dissolved in dimethoxyethane (30mL) in a container, and MeCpZrCl3 (0.921g, 3.33mmol) is added in batches as a solid.After stirring for about 12 hours, the solvent is removed in vacuo and the contents of the container are dissolved in dichloromethane (40mL) and filtered.NMR analysis of aliquots indicates the desired product.In order to purify the product, the volume of the filtrate is reduced to 20mL in a vacuum and hexane (20mL) is added. The solution was then stored in a glove box freezer (-32°C) to precipitate the recrystallized product, which was collected by filtration and washed with hexane (3 x 5 mL), then dried in vacuo to give methylcyclopentadienyl(1,5-dimethylindenyl)zirconium dichloride (0.527 g, 41.1%). 1 H NMR(C6D6): δ7.32(m,1H),6.93(m,1H),6.75(dd,1H),6.25(dd,1H),5.76(m,2H) ,5.58(m,1H),5.52(m,1H),5.38(td,1H),2.37(d,3H),2.09(d,3H),2.01(s,3H).

[0123] Embodiment 4, propyl cyclopentadienyl (1,5-dimethyl indenyl) zirconium dichloride is prepared as follows.1,5-dimethyl indenyl lithium is prepared as described in Example 2.In a glove box, 1,5-dimethyl indenyl lithium (0.500g, 3.33mmol) is dissolved in dimethoxyethane (30mL) in a container, and solid PrCpZrCl3 (DME) (1.315g, 3.33mmol) is added in batches.After stirring for about 12 hours, the solvent is removed in vacuo and the contents of the container are dissolved in toluene (50mL) and filtered.NMR analysis of aliquots indicates the desired product.In order to purify the product, the volume of the filtrate is reduced to 25mL in a vacuum and hexane (25mL) is added. The resulting mixture was heated to 60°C to dissolve and then stored in a glove box freezer (-32°C) to precipitate the recrystallized product, which was collected by filtration and washed with hexane (3×5 mL), then dried in vacuo to give propylcyclopentadienyl(1,5-dimethylindenyl)zirconium dichloride (0.893 g, 65.0%). 1 H NMR(C6D6): δ7.34(m,1H),6.96(m,1H),6.77(dd,1H),6.27(dd,1H),5.85(m,1H),5.81(dd,1H),5.68(d t,1H),5.57(td,1H),5.46(td,1H),2.47(td,2H),2.39(d,3H),2.11(d,3H),1.36(m,2H),0.75(t,3H).

[0124] 4,7-Dimethyl-1H-indene was prepared by one of the following two methods (Method A or Method B).

[0125] Method A

[0126] The 500mL two-necked round bottom container equipped with a magnetic stirring bar, a powder feed funnel containing aluminum chloride (16.04g, 120.3mmol), a nitrogen inlet and a purge to the outlet of the NaOH scrubber is flushed with dry nitrogen. Anhydrous dichloromethane (70mL) is loaded into the container, followed by p-xylene (14.91g, 140.5mmol) and 3-chloropropionyl chloride (13.35g, 105.1mmol), and then ice-water bath cooling is used. Excess aluminum chloride is then added by the powder feed funnel in 90min, and then the container is heated to 10°C, and then stirred for about 2 hours. The contents of the container are then poured on ice, causing the color to change from red to yellow. The organic layer is separated, and washed three times with water, dried over anhydrous magnesium sulfate, filtered, and vacuum condensed to form an intermediate, which is observed to be a yellow liquid. Then, sulfuric acid (60mL) was added to the container; the intermediate was added to the container by a syringe within 30 minutes, and the contents in the container were slowly heated to 65 ° C and kept at this temperature for two hours. The contents of the container were cooled to room temperature, poured on ice, and extracted with ether (100mL). The organic layer was washed with sodium bicarbonate solution and water, dried over anhydrous magnesium sulfate, and condensed in vacuo to give a crude product, which was observed to be a tan solid. Purification by column chromatography (SiO2, hexane: ethyl acetate = 90: 10) gave 4,7-dimethylindan-1-one, which was observed to be a light yellow / tan solid (11.82g, 70.43%).

[0127] 4,7-Dimethylindan-1-one (8.040 g, 50.18 mmol), methanol (150 mL) and THF (50 mL) were added to a 500 mL two-necked round bottom vessel equipped with a magnetic stirring bar, a removable lid and a reflux condenser with a nitrogen inlet. The contents of the vessel were cooled to a temperature of 5°C with an ice bath. Sodium borohydride (1.96 g, 51.81 mmol) was added to the vessel in portions over a period of 60 minutes through the removable lid while stirring; gas evolution was allowed to cease between each addition. The contents of the vessel were allowed to warm to room temperature and stirred for approximately 17 hours. The contents of the vessel were quenched by the addition of ice, concentrated in vacuo, and extracted with ethyl acetate. The organic layer was separated, dried over anhydrous magnesium sulfate, filtered and concentrated to give 4,7-dimethylindan-1-ol observed as a tan solid (7.56 g, 93.3%).

[0128] 4,7-Dimethylindan-1-ol (8.56 g, 52.8 mmol), toluene (800 mL) and p-toluenesulfonic acid (p-TSA) (0.188 g, 0.99 mmol) were added to a 1000 mL round bottom container equipped with a magnetic stirring bar and a reflux condenser with a nitrogen inlet. The contents of the container were heated at 45 ° C and the progress of the reaction was monitored by GC / MS. After 4 hours, molecular sieves were added to the container and heating was continued. After 6 hours, the reaction was quenched with a saturated sodium bicarbonate solution. The organic layer was separated, dried over anhydrous magnesium sulfate, filtered and concentrated to give a crude product, which was observed as a light yellow liquid. 4,7-Dimethyl-1H-indene was purified by column chromatography (SiO2, hexane) and observed as a colorless liquid (5.68 g, 74.7%).

[0129] Method B

[0130] A solution of sodium methoxide in methanol (5M, 170.5 mL, 852.5 mmol) was charged into a 3-neck round bottom container; the contents of the container were cooled to 0°C. Freshly cracked and distilled cyclopentadiene (34.3 mL, 511.5 mmol) was added to the container over 20 minutes. The contents of the container were stirred for about 2 hours under a nitrogen atmosphere and at a temperature of 0°C. 2,5-hexanedione (40 mL, 340.9 mmol) was added dropwise over 30 minutes using an addition funnel. The contents of the container were stirred at ambient temperature for about 12 hours. Volatiles were removed under vacuum, and water (150 mL) and ether (250 mL) were added. The organic layer and the aqueous layer were separated, and the aqueous layer was extracted twice with ether (50 mL). The organic layer was washed with saturated sodium chloride, dried over magnesium sulfate and the solvent was removed under vacuum. Purification by distillation (bp 65°C, 0.01 mmHg) gave 4,7-dimethyl-1H-indene observed as a light yellow oil (35 g, 71% yield). Other synthetic steps discussed herein can be performed using 4,7-dimethyl-1H-indene obtained by either Method A or Method B.

[0131] Comparative Example A, cyclopentadienyl(4,7-dimethylindenyl)zirconium dimethyl was prepared as follows.

[0132] 4,7-Dimethyl-1H-indene (5.60 g, 39.4 mmol) was dissolved in hexane (100 mL) in a 200 mL glass container equipped with a stirring bar. A solution of n-butyl lithium in hexane (2.5 M, 17 mL, 43 mmol) was slowly added to the container at room temperature. The contents of the container were stirred at room temperature for about 17 hours, and the resulting white precipitate was collected by vacuum filtration, washed with hexane, and vacuum dried to give 4,7-dimethylindenyl lithium (5.27 g, 90.4%), which was observed as an off-white solid.

[0133] Diethyl ether (100 mL) containing 4,7-dimethylindenyl lithium (2.33 g, 15.5 mmol) was added to a glass container (110 mL) equipped with a stirring bar. CpZrCl3·DME (5.50 g, 15.6 mmol) and diethyl ether (20 mL) were added to the container, resulting in the immediate formation of a bright yellow solution and precipitate observed. The contents of the container were stirred for approximately 17 hours, then diluted with dichloromethane (80 mL) and filtered. The filtrate was concentrated under vacuum to give cyclopentadienyl (4,7-dimethylindenyl) zirconium dichloride, observed as a bright yellow solid (3.72 g, 65.1%).

[0134] Comparative Example B, methylcyclopentadienyl(4,7-dimethylindenyl)zirconium dimethyl was prepared as follows.

[0135] 4,7-dimethylindenyl lithium was prepared as described above. Ether (100 mL) containing 4,7-dimethylindenyl lithium (0.800 g, 5.33 mmol) was added to a glass container (200 mL) equipped with a stirring rod. MeCpZrCl3·DME (1.95 g, 5.34 mmol) was added to the container, resulting in the immediate formation of a bright yellow solution and precipitate observed. The contents of the container were stirred for approximately 17 hours, then diluted and filtered with dichloromethane (20 mL). The filtrate was concentrated under vacuum, and the resulting yellow solid was suspended in hexane (100 mL) and collected by vacuum filtration. The crude residue was first recrystallized from ether (20 mL) and dichloromethane (10 mL), and then recrystallized from toluene (40 mL) and hexane (10 mL). The crystals were collected and dried under vacuum to give methylcyclopentadienyl(4,7-dimethylindenyl)zirconium dichloride observed as a bright yellow solid (0.471 g, 23.1%).

[0136] Polymerization catalyst Example 1-CAT was prepared as follows. Treated fumed silica (Cabosil TS-610; 1.33 g) was slurried in toluene (38 g), followed by the addition of a 10% by weight solution of methylaluminoxane (MAO) in toluene (11 g). Next, Example 1 (0.42 g) was added and the mixture was stirred for approximately 45 minutes and then introduced into an atomizer. The droplets produced by the atomizer were then contacted with a stream of hot nitrogen to evaporate the liquid and form a powder. The powder was separated from the gas mixture in a cyclone separator and discharged into a container. The spray dryer temperature was set to 140°C and the outlet temperature was set to 75°C. Example 1-CAT was collected in the form of a fine powder. The load was maintained at a constant 50umol / g, corresponding to an Al:Zr ratio of approximately 100.

[0137] Polymerization Catalyst Example 2-CAT was prepared as Example 1-CAT, except that Example 2 was used instead of Example 1.

[0138] Polymerization Catalyst Example 3-CAT was prepared as Example 1-CAT, except that Example 3 was used instead of Example 1.

[0139] Example 4-CAT was prepared as Example 1-CAT, except that Example 4 was used instead of Example 1.

[0140] Comparative Example A-CAT was prepared as Example 1-CAT, except Comparative Example A was used instead of Example 1.

[0141] Comparative Example B-CAT was prepared as Example 1-CAT, except Comparative Example B was used instead of Example 1.

[0142] Polymerizations using Comparative Example B-CAT were conducted using a gas phase pilot reactor operating at 105° C., a C6 / C2 ratio of 0.0050, a H2 / C2 ratio of 0.0020, 9 mole percent isopentane, and an ethylene partial pressure of 220 psi. Thereafter, a number of polymer properties were determined, such as melt index (I2) as determined in accordance with ASTM D1238-13 (at 190° C., 2.16 kg load); catalyst activity (grams polymer / gram catalyst-hour) as determined by the ratio of polymer yield to the amount of catalyst added to the reactor; melting temperature (T) as determined by differential scanning calorimetry in accordance with ASTM D 3418-08. m ); density determined according to ASTM D-792-13; Mn, Mw, Mz and Mw / Mn determined by gel permeation chromatography (GPC). The results are reported in Table 1.

[0143] Based on the polymerization of Comparative Example B-CAT, Example 1-CAT, Example 2-CAT, and Comparative Example A-CAT are expected to have the melt index, catalyst activity, melt temperature, density, Mn, Mw, Mz, and Mw / Mn as reported in Table 1.

[0144] Table 1

[0145]

[0146] The data in Table 1 demonstrate that the polymers formed using each of Example 1-CAT and Example 2-CAT are expected to have surprising and improved, i.e., reduced, melt indexes (I2) compared to polymers formed using each of Comparative Example A-CAT and Comparative Example B-CAT.

[0147] The data in Table 1 also demonstrate that the polymers formed using each of Example 1-CAT and Example 2-CAT are expected to have surprising and improved, ie, increased, melting temperatures compared to the polymers formed using each of Comparative Example A-CAT and Comparative Example B-CAT.

[0148] The data in Table 1 also demonstrate that the polymers formed using each of Example 1-CAT and Example 2-CAT are expected to have surprising and improved, i.e., increased, molecular weight (Mn, Mw and / or Mz) compared to the polymers formed using each of Comparative Example A-CAT and Comparative Example B-CAT.

[0149] The data in Table 1 also demonstrate that the polymers formed using each of Example 1-CAT and Example 2-CAT are expected to have surprising and improved, ie, increased, density compared to the polymers formed using each of Comparative Example A-CAT and Comparative Example B-CAT.

[0150] 1,4-dimethylindenyl lithium was synthesized as follows. A solution of 4-methyl-1-indanone (5.00 g, 34.2 mmol) in THF (20 mL) was added to a container including a solution of methylmagnesium bromide (3.0 M in ether, 22.8 mL, 68 mmol) in THF (50 mL) at a temperature of about 0°C over 15 min. The contents of the container were stirred at room temperature for 3 hours, and then cooled in a dry ice / acetone bath, and 15% HCl (100 mL) was slowly added in a fume hood under a nitrogen purge. The contents of the container were stirred while warming to room temperature. Ether (40 mL) was added and the organic layer was separated. The aqueous fraction was extracted with ether (3×40 mL), and the combined organic fractions were washed with saturated sodium bicarbonate, water, and brine; and then dried over magnesium sulfate. After filtering and evaporating the volatiles from the filtrate, the crude dimethylindene was dissolved in hexanes (about 60 mL), passed through silica gel, and treated with BuLi (21 mL, 33.6 mmol). After stirring for about 12 hours, the 1,4-dimethylindenyl lithium was collected by filtration, washed with hexanes, and dried in vacuo. Yield = 4.441 g (86.5%) of a white solid. 1 H NMR(400MHz,THF-d8)δ7.14(dq,J=8.1,0.8Hz,1H),6.42(dd,J=8.1,6.5Hz,1H),6.30(dd,J=3.1,0.7Hz,1 H), 6.28 (dp, J = 6.5, 0.9Hz, 1H), 5.73 (dd, J = 3.2, 0.8Hz, 1H), 2.41 (d, J = 0.6Hz, 3H), 2.40 (d, J = 0.7Hz, 4H).

[0151] 1,6-Dimethylindenyl lithium was synthesized as follows. 6-Methyl-1-indanone (3.00 g, 20.52 mmol) was dissolved in toluene (20 mL) under a nitrogen atmosphere and cooled to about -35 °C. Trimethylaluminum (2.0 M in toluene, 21.6 mL, 43.1 mmol) was added and the resulting mixture was stirred overnight and then diluted with ether (100 mL) and cooled in an ice bath, and quenched by adding 6M HCl (30 mL) under a stream of nitrogen. The resulting biphasic mixture was stirred for about 2 hours to convert to dimethylindene. The organic layer was separated and washed with water (2×40 mL), saturated sodium bicarbonate (40 mL), and brine (40 mL); dried with magnesium sulfate; and filtered. The resulting mixture was concentrated on a rotary evaporator at 100 torr for about one hour, then placed in a glove box, diluted with hexane (80 mL), and filtered through silica. n-Butyllithium (1.6 M in hexanes, 12.8 mL, 20.5 mmol) was added and the mixture was stirred for approximately three days.The white precipitate was collected by filtration, washed thoroughly with hexanes (3 x 20 mL) and dried under vacuum to give 1,6-dimethylindenyllithium (2.561 g). 1 H NMR (400MHz, THF-d8) δ7.16 (dd, J=8.1, 0.7Hz, 1H), 7.03 (dq, J=1.8, 0.9Hz, 1H), 6.30 (dd, J=8.1, 1. 7Hz, 1H), 6.26 (d, J = 3.2, 1H), 5.65 (dd, J = 3.2, 0.8Hz, 1H), 2.40–2.37 (m, 3H), 2.32 (d, J = 0.9Hz, 3H).

[0152] 1,7-Dimethylindenyl lithium was synthesized as follows. The synthesis described for 1,6-dimethylindenyl lithium was repeated except that 7-methyl-1-indanone (4.795 g, 32.80 mmol) was used. The yield was 4.152 g (84.31%) of 1,7-dimethylindenyl lithium. 1 H NMR(400MHz,THF-d8)δ7.07(d,J=8.1Hz,1H),6.28(dd,J=8.1,6.5Hz,1H),6.24–6.18(m,1H),6 .12(dp,J=6.5,1.0Hz,1H),5.66(d,J=3.1Hz,1H),2.68(d,J=0.7Hz,3H),2.66(t,J=0.7Hz,3H).

[0153] 1,5,7-Trimethylindenyl lithium was synthesized as follows. The synthesis described for 1,6-dimethylindenyl lithium was repeated, except that 5,7-dimethyl-1-indanone (5.00 g, 31.2 mmol) was used and ether (approximately 1 mL) was added to the reaction mixture after the n-BuLi addition step. 1,5,7-trimethylindenyl lithium was obtained as a white solid. Yield = 4.133 g (80.7%). 1 H NMR (400MHz, THF-d8) δ6.84(s,1H),6.14(d,J=3.0Hz,1H),6.00(s,1H),5.56(d,J=3.1Hz,1H),2.66–2.64(m,3H),2.62(s,3H),2.21(d,J=0.8Hz,3H).

[0154] 1-Ethyl-5-methyl-indenyl lithium was synthesized as follows. The synthesis of 1,4-dimethyl-indenyl lithium was repeated except that 5-methyl-1-indanone (5.00 g, 34.2 mmol) and ethylmagnesium bromide (3.0 M in diethyl ether, 22.8 mL, 68 mmol) were used. 1-Ethyl-5-methyl-indenyl lithium was obtained as a light orange solid (yield = 4.192 g). 1 H NMR(400MHz,THF-d8)δ7.22(dt,J=8.1,0.9Hz,1H),7.04(dq,J=1.8,0.9Hz,1H),6.33–6.29(m,2H),5 .62(dd,J=3.1,0.8Hz,1H), 2.84(qd,J=7.5,0.6Hz,2H), 2.29(d,J=0.9Hz,4H), 1.26(t,J=7.5Hz,3H).

[0155] Example 5, cyclopentadienyl (1,4-dimethylindenyl) zirconium dichloride is synthesized as follows. In a glove box, 1,4-dimethylindenyl lithium (0.500g, 3.33mmol) is dissolved in dimethoxyethane (30mL) and added to a container. Cyclopentadienyl zirconium trichloride (0.875g, 3.33mmol) in solid form is added to the container in batches. The contents of the container are stirred for about 48 hours. The solvent is then removed in vacuo and the residue is dissolved in toluene (80mL), filtered through diatomaceous earth, and washed with additional toluene (2×10mL). The solvent in the filtrate is removed in vacuo, and the residue is recrystallized from a dichloromethane solution (about 7mL) by layering hexane (about 20mL) on top. The product is separated by decantation, rinsed with hexane and dried in vacuo to give a bright yellow solid. Yield = 0.686g (65.3%). 1H NMR (400MHz, benzene-d6) δ7.28 (dq, J=8.5, 0.8Hz, 1H), 6.92 (dd, J=8.6, 6.7Hz, 1H), 6.73 (dp, J= 6.7,1.1Hz,1H),6.09–5.97(m,1H),5.83(dd,J=3.2,0.9Hz,1H),5.78(s,5H),2.21(s,6H).

[0156] Example 6, cyclopentadienyl (1,6-dimethylindenyl) zirconium dichloride is synthesized as follows. Cyclopentadienyl zirconium trichloride (0.875g, 3.33mmol) is dissolved in dimethoxyethane (40mL) and added to a container. 1,6-dimethylindenyl lithium (0.500g, 3.33mmol) in solid form is added to the container in batches. The contents of the container are stirred for about 48 hours. The solvent is then removed in vacuo and the residue is dissolved in a mixture of dichloromethane (40mL) and hexane (30mL) and filtered. The volume of the filtrate is reduced to 55mL with vacuum and stored in a refrigerator. The product crystallizes as a yellow solid at a reduced temperature, which is collected by filtration, washed with hexane (3×5mL) and dried in vacuo. Yield = 0.681g (55.2%). 1 HNMR (400MHz, benzene-d6) δ7.24 (tq, J=2.1, 1.0Hz, 1H), 7.03 (dt, J=8.5, 0.6Hz, 1H), 6.72 (dd, J=8.6, 1.5Hz, 1H), 6.2 1(dd,J=3.2,0.7Hz,1H),5.77(s,5H),5.75(dd,J=3.2,0.9Hz,1H),2.37(d,J=0.6Hz,3H),2.11(d,J=1.1Hz,3H).

[0157] Example 7, cyclopentadienyl (1,7-dimethylindenyl) zirconium dichloride is synthesized as follows. Cyclopentadienyl zirconium trichloride (0.875g, 3.33mmol) is dissolved in dimethoxyethane (40mL) and added to a container. 1,7-dimethylindenyl lithium (0.500g, 3.33mmol) is added to the container in batches as a solid. The contents of the container are stirred for about 4 hours. The solvent is then removed in vacuo and the residue is dissolved in toluene (50mL) and filtered. The solvent is removed in vacuo, and the product is recrystallized from a mixture of toluene (~40mL) and hexane (~10mL) by dissolving at 55°C and cooling to -35°C to obtain 0.844g (68.4%) of the product as a bright yellow solid. 1H NMR (400MHz, benzene-d6) δ6.95–6.89(m,1H),6.73(dd,J=8.5,6.8Hz,1H),6.60(dp,J=6.8,1.1Hz,1H),6.17( dd,J=3.2,0.7Hz,1H),5.77(s,5H),5.63(d,J=3.2Hz,1H),2.55(d,J=0.6Hz,3H),2.52(d,J=1.0Hz,3H).

[0158] Example 8, cyclopentadienyl (1,5,7-trimethylindenyl) zirconium dichloride is synthesized as follows. 1,5,7-trimethylindenyl lithium (0.150g, 0.914mmol) is dissolved in dimethoxyethane (20mL) and added to a container. Cyclopentadienyl zirconium trichloride (0.240g, 0.914mmol) in a solid state is added to the container in batches. The contents of the container are stirred for about 12 hours. The solvent is then removed by vacuum and the residue is dissolved in toluene (about 60mL) and filtered. The volume of the filtrate is reduced to 30mL with vacuum, heated to 50°C to dissolve, and trace amounts of white solids are removed by filtration again, and recrystallized from a solvent mixture of toluene (15mL) and hexane (7mL) at a reduced temperature to obtain a product in the form of a bright yellow solid. Yield = 0.097g (27.7%). 1 H NMR (400 MHz, CHLOROFORM-d) δ 7.19 (s, 1H), 6.79 (t, J = 1.3 Hz, 1H), 6.47 (d, J = 3.2 Hz, 1H), 6.20 (d, J = 3.2 Hz, 1H), 6.17 (s, 5H), 2.70 (d, J = 0.5 Hz, 3H), 2.66 (t, J = 0.8 Hz, 3H), 2.40 (d, J = 1.0 Hz, 3H).

[0159] Embodiment 9, cyclopentadienyl (1-ethyl-5-methyl indenyl) zirconium dichloride is synthesized as follows.1-ethyl-5-methyl indenyl lithium (0.600g, 3.33mmol) is dissolved in dimethoxyethane (30mL) and added to a container.Cyclopentadienyl zirconium trichloride (0.960g, 3.33mmol) in solid form is added to the container in batches.The contents of the container are stirred for about 12 hours.Then vacuum removes the solvent and the residue is dissolved in dichloromethane (30mL) and filtered through diatomaceous earth, and washed with other dichloromethane (3×10mL).The volume of the filtrate is reduced to 20mL with vacuum, hexane (10mL) is added, and the product crystallizes at a reduced temperature, is collected by filtration, washed with hexane (2×10mL), and vacuum dried to obtain 0.761g. 1H NMR (400MHz, chloroform-d) δ7.53(d,J=8.7Hz,1H),7.39(m,1H),7.11(dd,J=8.7,1.5Hz,1H),6.62(d,J=3.2Hz,1H) ,6.32(dd,J=3.2,0.8Hz,1H),6.13(s,5H),3.11–2.79(m,2H),2.47(d,J=1.2Hz,3H),1.28(t,J=7.5Hz,4H).

[0160] Example 10, methylcyclopentadienyl (1,4-dimethylindenyl) zirconium dichloride is synthesized as follows. 1,4-dimethylindenyl lithium (0.500g, 3.33mmol) is dissolved in dimethoxyethane (30mL) and added to a container. Methylcyclopentadienyl zirconium trichloride (0.921g, 3.33mmol) in solid form is added to the container in batches. The contents of the container are stirred for about 12 hours. The solvent is then removed in vacuo and the residue is dissolved in toluene (50mL) and filtered at room temperature, and washed with more toluene (2×15mL). The product is crystallized from a solvent mixture of toluene (20mL) and hexane (20mL) at a reduced temperature, collected by filtration and washed with hexane to obtain 1.027g of a product with about 94% purity (by NMR). For further purification, it is dissolved in dichloromethane (10mL), and hexane (25mL) is carefully added as the top layer. After approximately 12 hours, the precipitated crystalline product was collected by decantation, washed with hexanes and dried in vacuo to give 0.569 g (44.4%) of the product. 1 H NMR (400MHz, chloroform-d) δ7.49 (dq, J=8.6, 0.8Hz, 1H), 7.22 (dd, J=8.6, 6.7Hz, 1H), 7. 05(dp,J=6.7,1.0Hz,1H),6.62(d,J=3.3Hz,1H),6.38(dd,J=3.2,0.9Hz,1H),6.0 0(q,J=2.6Hz,1H),5.97(q,J=3.8,3.2Hz,1H),5.94(td,J=3.1,2.4Hz,1H),5.87( td,J=3.1,2.3Hz,1H),2.46(d,J=1.0Hz,3H),2.46(d,J=0.6Hz,3H),2.18(s,3H).

[0161] Example 11, methylcyclopentadienyl (1,6-dimethylindenyl) zirconium dichloride was synthesized as follows. Methylcyclopentadienyl zirconium trichloride (0.921 g, 3.33 mmol) was dissolved in dimethoxyethane (30 mL) and added to a container. 1,6-dimethylindenyl lithium (0.500 g, 3.33 mmol) was added to the container in batches as a solid. The contents of the container were stirred for approximately 1.5 hours and then filtered to remove some salts; the solvent in the filtrate was removed by vacuum. The residue was dissolved in hexane (35 mL) and dichloromethane (30 mL), heated to 40° C. and filtered again. The clear filtrate was concentrated to 45 mL and stored in a refrigerator to produce a yellow crystalline solid, which was collected by filtration, washed with hexane (3×5 mL) and dried in vacuo. Yield = 0.646 g (50.5%). 1 H NMR (400MHz, benzene-d6) δ7.24 (tt, J=2.0, 1.0Hz, 1H), 7.09 (dd, J=8.7, 0.9Hz, 1H), 6.74 (dd, J= 8.7,1.6Hz,1H),6.26(dd,J=3.3,0.7Hz,1H),5.81(dd,J=3.2,0.9Hz,1H),5.75(dtd,J=2. 9,2.3,0.6Hz,1H),5.59(dtd,J=2.9,2.3,0.6Hz,1H),5.51(td,J=3.1,2.3Hz,1H),5.40(t d,J=3.1,2.3Hz,1H),2.38(d,J=0.6Hz,3H),2.11(d,J=1.0Hz,3H),2.02(d,J=0.6Hz,3H).

[0162] Example 12, methylcyclopentadienyl (1,7-dimethylindenyl) zirconium dichloride is synthesized as follows. Methylcyclopentadienyl zirconium trichloride (0.921g, 3.33mmol) is dissolved in dimethoxyethane (40mL) and added to a container. 1,7-dimethylindenyl lithium (0.500g, 3.33mmol) in a solid state is added to the container in batches. The contents of the container are stirred for about 16 hours. The solvent is then removed in vacuo and the residue is dissolved in toluene (60mL), heated to about 60°C and filtered. The solvent in the filtrate is removed in vacuo to obtain a product (1.250g) in the form of a yellow solid. The product is recrystallized from a solvent mixture of toluene (45mL) and hexane (12mL) at a reduced temperature. Yield = 0.985g (77.0%). 1H NMR (400MHz, chloroform-d) δ7.43 (dp, J=8.5, 0.8Hz, 1H), 7.11 (dd, J=8.5, 6.8Hz, 1H), 6. 92(dp,J=6.8,1.1Hz,1H),6.53(dd,J=3.2,0.7Hz,1H),6.28(d,J=3.2Hz,1H),6. 12–6.07(m,1H),5.96(td,J=3.1,2.3Hz,1H),5.87–5.82(m,1H),5.80(td,J=3.1 ,2.3Hz,1H),2.74(d,J=0.6Hz,3H),2.70(d,J=0.9Hz,3H),2.17(d,J=0.6Hz,3H).

[0163] Example 13, methylcyclopentadienyl (1,5,7-trimethylindenyl) zirconium dichloride is synthesized as follows. Methylcyclopentadienyl zirconium trichloride (0.914g, 3.30mmol) is dissolved in dimethoxyethane (20mL) and added to a container. 1,5,7-trimethylindenyl lithium (0.543g, 3.30mmol) in solid form is added to the container in batches. The contents of the container are stirred for about 12 hours. The solvent is then removed in vacuo and the residue is dissolved in dichloromethane (20mL) and filtered at 35°C. The solvent in the filtrate is removed in vacuo to obtain the product (1.377g). The product is recrystallized from a mixture of dichloromethane (25mL) and hexane (25mL) at a reduced temperature to obtain a bright yellow solid. The yield is 0.793g (60.2%). 1 H NMR (400MHz, chloroform-d) δ7.18(td,J=1.7,0.8Hz,1H),6.77(q,J=1.3Hz,1H),6.46(d d,J=3.1,0.7Hz,1H),6.16(d,J=3.1Hz,1H),6.11–6.06(m,1H),5.96(td,J=3.1, 2.3Hz, 1H), 5.85 (qd, J=2.6, 1.4Hz, 1H), 5.77 (td, J=3.1, 2.3Hz, 1H), 2.70 (d, J= 0.6Hz, 3H), 2.66 (t, J = 0.9Hz, 3H), 2.39 (d, J = 1.1Hz, 3H), 2.16 (d, J = 0.6Hz, 3H).

[0164] Example 14, propylcyclopentadienyl (1,5-dimethylindenyl) zirconium dichloride is synthesized as follows. Propylcyclopentadienyl zirconium trichloride, DME adduct (1.315g, 3.33mmol) is dissolved in dimethoxyethane (40mL) and added to a container. 1,5,7-trimethylindenyl lithium (0.500g, 3.33mmol) in solid form is added to the container in batches. The contents of the container are stirred for about 7 hours. The solvent is then removed in vacuo and the residue is dissolved in toluene (50mL) and filtered. The volume of the filtrate is reduced to 25mL, hexane (25mL) is added, and the product is recrystallized as a yellow solid at a reduced temperature, which is collected by filtration, washed with hexane (3×5mL) and dried in vacuo. Yield = 0.893g (65.0%). 1 H NMR (400MHz, benzene-d6) δ7.35(dd,J=8.7,1.0Hz,1H),6.96(h,J=1.0Hz,1H),6.77(dd,J=8.8,1.5Hz,1 H),6.27(dd,J=3.1,0.7Hz,1H),5.85(dt,J=3.0,2.3Hz,1H),5.81(dd,J=3.1,0.9Hz,1H),5.68(d t,J=3.0,2.3Hz,1H),5.57(td,J=3.1,2.3Hz,1H),5.46(td,J=3.1,2.3Hz,1H),2.47(td,J=7.5,3 .6Hz, 2H), 2.39 (d, J = 0.6Hz, 3H), 2.11 (d, J = 1.2Hz, 3H), 1.43–1.30 (m, 2H), 0.75 (t, J = 7.4Hz, 3H).

[0165] Example 15, propylcyclopentadienyl (1,6-dimethylindenyl) zirconium dichloride is synthesized as follows. Propylcyclopentadienyl zirconium trichloride, DME adduct (1.315g, 3.33mmol) is dissolved in dimethoxyethane (40mL) and added to a container. 1,6-dimethylindenyl lithium (0.500g, 3.33mmol) is added to the container in batches as a solid. The contents of the container are stirred for about 12 hours. The solvent is then removed in vacuo, and the residue is dissolved in toluene (50mL) and filtered. Toluene in the filtrate is removed in vacuo to obtain 1.310g of product, which is recrystallized from a solvent mixture of dichloromethane (15mL) and hexane (30mL) at a reduced temperature as a yellow solid, which is collected by filtration, washed with hexane (3×5mL) and dried in vacuo. Yield = 0.6621g (48.2%). 1H NMR (400MHz, benzene-d6) δ7.26(tt,J=2.0,1.0Hz,1H),7.09(dd,J=8.6,0.9Hz,1H),6.75(dd,J =8.7,1.5Hz,1H),6.27(dd,J=3.2,0.7Hz,1H),5.83(td,J=3.0,0.8Hz,2H),5.66(dt,J=3. 0,2.3Hz,1H),5.54(td,J=3.1,2.3Hz,1H),5.46(td,J=3.1,2.3Hz,1H),2.53–2.44(m,2H ), 2.39 (d, J = 0.6Hz, 3H), 2.11 (d, J = 1.1Hz, 3H), 1.43–1.30 (m, 2H), 0.75 (t, J = 7.3Hz, 3H).

[0166] Example 16, propylcyclopentadienyl (1,7-dimethylindenyl) zirconium dichloride is synthesized as follows. Propylcyclopentadienyl zirconium trichloride, DME adduct (1.315g, 3.33mmol) is dissolved in dimethoxyethane (40mL) and added to a container. 1,7-dimethylindenyl lithium (0.500g, 3.33mmol) is added to the container in batches as a solid. The contents of the container are stirred for about 16 hours. The solvent is then removed in vacuo, and the residue is dissolved in toluene (50mL) and filtered. The solvent in the filtrate is removed in vacuo to obtain a product in the form of a high-purity yellow solid. Yield = 1.316g (95.8%). 1 H NMR (400MHz, benzene-d6) δ6.99 (dp, J=8.5, 0.8Hz, 1H), 6.77 (dd, J=8.5, 6.8Hz, 1H), 6.61 (dp, J=6.8, 1.1H z,1H),6.24(dd,J=3.2,0.7Hz,1H),5.87(dt,J=3.0,2.3Hz,1H),5.70(d,J=3.2Hz,1H),5.65(dt,J= 2.9,2.3Hz,1H),5.57(td,J=3.1,2.3Hz,1H),5.43(td,J=3.1,2.3Hz,1H),2.58(d,J=0.6Hz,3H),2. 54(t,J=1.0Hz,3H), 2.49(td,J=7.5,3.3Hz,2H), 1.37(dt,J=7.9,7.3Hz,2H), 0.75(t,J=7.3Hz,3H).

[0167] Example 17, propylcyclopentadienyl (1,5,7-trimethylindenyl) zirconium dichloride is synthesized as follows. Propylcyclopentadienyl zirconium trichloride, DME adduct (1.203g, 3.05mmol) is dissolved in dimethoxyethane (40mL) and added to a container. 1,5,7-trimethylindenyl lithium (0.500g, 3.05mmol) in solid form is added to the container in batches. The contents of the container are stirred for about 48 hours. The solvent is then removed in vacuo, and the residue is dissolved in toluene (60mL) and filtered. The volume of the filtrate is reduced to 25mL with vacuum, hexane (25mL) is added, and the product is crystallized at a reduced temperature. The product is collected by filtration and washed with hexane (3×5mL), then dried in vacuo. Yield = 0.895g (68.9%). 1 H NMR (400 MHz, chloroform-d) δ7.21–7.15 (m, 1H), 6.77 (t, J = 1.3 Hz, 1H), 6.45 (dd, J = 3.2, 0.7 Hz, 1H), 6.16 (d, J = 3.2 Hz, 1H), 6.13–6.08 (m, 1H), 5.94 (td, J = 3.1, 2.3 Hz, 1H), 5.90–5.85 (m, 1H),5.81(td,J=3.1,2.3Hz,1H),2.70(d,J=0.6Hz,3H),2.65(t,J=0.9Hz,3H),2.48(td ,J=7.5,5.5Hz,2H),2.39(d,J=1.1Hz,3H),1.51(q,J=7.5Hz,2H),0.89(t,J=7.3Hz,3H).

[0168] It is expected that the polymers formed using the polymerization catalysts prepared by each of Examples 5 to 17, respectively, can have surprising and improved, i.e., reduced, melt indexes (I2) compared to the polymers formed using each of Comparative Examples A-CAT and Comparative Example B-CAT.

[0169] It is expected that polymers formed using the polymerization catalysts prepared from each of Examples 5 to 17, respectively, may have surprising and improved, ie, increased, melting temperatures compared to polymers formed using each of Comparative Example A-CAT and Comparative Example B-CAT.

[0170] It is expected that the polymers formed using the polymerization catalysts prepared by each of Examples 5 to 17, respectively, can have surprising and improved, i.e., increased, molecular weights (Mn, Mw and / or Mz) compared to the polymers formed using each of Comparative Example A-CAT and Comparative Example B-CAT.

[0171] It is expected that polymers formed using the polymerization catalysts prepared from each of Examples 5 to 17, respectively, may have surprising and improved, ie, increased, density compared to polymers formed using each of Comparative Example A-CAT and Comparative Example B-CAT.

Claims

1. A metal-ligand complex of formula I: wherein M is titanium, zirconium or hafnium; R is hydrogen or a C1 to C4 alkyl group; R 1 is C1 to C4 alkyl; R 2 , R 3 , R 4 Any one of C1 to C 20 Alkyl and R 2 , R 3 , R 4 Two of them are H; R 5 is H; and each X is independently halogen, C1 to C 20 Alkyl, C7 to C 20 Arylalkyl, C1 to C6 alkyl-substituted C6 to C 12 Aryl or silane-containing.

2. The metal-ligand complex according to claim 1, wherein R 1 is a C1 alkyl group, R 2 is hydrogen, R 3 is hydrogen, R 4 is a C1 alkyl group, and the metal-ligand complex is represented by Formula II: wherein R is hydrogen or C1 to C2 alkyl, M is titanium, zirconium or hafnium, and wherein each X is independently a halogen, C1 to C 20 Alkyl, C7 to C 20 Arylalkyl, C1 to C6 alkyl-substituted C6 to C 12 an aryl group, a C1 to C6 alkyl-substituted benzyl group, or a silyl-containing group.

3. The metal-ligand complex according to claim 1 or claim 2, wherein R is hydrogen.

4. The metal-ligand complex according to claim 1 or claim 2, wherein R is a C1 to C2 alkyl group.

5. The metal-ligand complex according to claim 1 or claim 2, wherein R is a methyl group.

6. The metal-ligand complex according to claim 1 or claim 2, wherein R is ethyl.

7. The metal-ligand complex according to claim 1 or claim 2, wherein M is Zr.

8. The metal-ligand complex according to claim 1 or claim 2, wherein each X is independently Cl, C1 to C3 alkyl or benzyl.

9. The metal-ligand complex according to claim 1 or claim 2, which is selected from: A metal-ligand complex of formula I wherein R is hydrogen, M is zirconium, and each X is Cl; A metal-ligand complex of formula I wherein R is methyl, M is zirconium, and each X is Cl; A metal-ligand complex of formula I wherein R is ethyl, M is zirconium, and each X is Cl; A metal-ligand complex of formula I wherein R is hydrogen, M is zirconium, and each X is methyl; A metal-ligand complex of formula I wherein R is methyl, M is zirconium, and each X is methyl; and The metal-ligand complex of formula I wherein R is ethyl, M is zirconium, and each X is methyl.

10. A method for preparing a polymerization catalyst, comprising contacting the metal-ligand complex according to claim 1 or claim 2 with an activator under activation conditions to activate the metal-ligand complex, thereby preparing the polymerization catalyst.

11. The method of claim 10, wherein the activator is methylaluminoxane.

12. A polymerization catalyst prepared by the method according to claim 10.

13. A method for preparing a polyolefin polymer, comprising: The polyolefin polymer is prepared by contacting an olefin with the polymerization catalyst according to claim 12 under polymerization conditions to polymerize the olefin.

Citation Information

Patent Citations

  • Process for gas phase polymerization of olefin

    EP0634421A1

  • Staged reactor polymerisation process

    EP0794200A2

  • Fluidized bed polymerization reactor

    EP0802202A1

  • Modified polyethylene compositions

    US20060173123A1

  • A polyolefin composition and method of producing the same

    US20180002464A1